Realizing Inclusion and Systemic Equity in Medicine: Upstanding in the Medical Workplace (RISE UP)-an Antibias Curriculum - Sarah J. Calardo; Maybelle Kou; Courtney Port; Natalie McKnight; B. Elise Switzer; Kamilah Halmon; Kenia Lobo; Ghofrane Benghanem; Patricia W. Seo-Mayer (Association of American Medical Colleges, 2022)
Introduction Racism is a public health threat, and racist behaviors adversely affect clinicians in addition to patients. Medical trainees commonly experience racism and bias. More than half of pediatric residents at a single institution reported experiencing or witnessing discriminatory behavior at work; only 50% reported receiving training on implicit bias, delivering difficult feedback, or peer support. Our multispecialty team created Realizing Inclusion and Systemic Equity in Medicine: Upstanding in the Medical Workplace (RISE UP), an antibias, anti-racism communication curriculum composed of three hybrid (virtual and in-person) workshops. Methods During the pediatric resident workshops, we introduced tools for addressing bias, presented video simulations, and led small-group debriefings with guided role-play. We also reviewed escalation pathways, reporting methods, and support systems. Residents completed an evaluation before and after each workshop to assess the curriculum's efficacy. Results Thirty-nine residents participated in RISE UP, with 20 attending all three workshops. Ninety-six percent of participants indicated they would recommend the workshops to colleagues. After the third workshop, 92% reported having tools to respond to bias, and 85% reported knowing how to escalate concerns regarding discriminatory behavior. Chief residents were most frequently identified as sources of resident support when encountering discriminatory behavior. Discussion This curriculum was successful in developing and strengthening residents' responses to discrimination, including upstander support. The curriculum is adaptable for virtual, in-person, and hybrid settings, allowing for flexibility. Establishing institutional support, promoting faculty development, and creating and disseminating escalation pathways are critical to addressing racism in health care.